Community Forest Stewardship and Its Role in Strengthening Local Environmental Resilience - Asikin Muchtar (PT FORMOSA CENDEKIA GLOBAL, 2026)
Community-based forest management is an important approach in dealing with increasing local environmental vulnerabilities due to climate change, ecosystem degradation, and socio-economic pressures. This study aims to analyze the role of community forest stewardship in strengthening local environmental resilience by placing the community as the main actor in forest management. The research uses a qualitative approach with a case study design in North Luwu Regency, South Sulawesi. Data were collected through semi-structured in-depth interviews with ten key informants comprising community-based forest managers, indigenous leaders, forest-dependent residents, and village officials, and supported by field observation and analysis of policy and environmental documents. The data was analyzed using thematic analysis. The results show that community-based forest management plays a role in maintaining ecosystem balance, reducing the risk of environmental damage, and increasing the adaptive capacity of communities through the application of local norms, collective management, and sustainable forest utilization. This study concludes that community forest stewardship is an effective strategy in strengthening local environmental resilience and provides important implications for the development of inclusive and sustainable social forestry policies.